Comparative Economic Discourse in Journalism: A Sociological and Educational Perspective on Albanian and Italian Terminology - Himçi, Denis; Shopi, Meleq; Zekaj, Xhevdet (European Journal of Social Science Education and Research, 2026)
This study examines economic discourse in contemporary Albanian journalism, with a comparative focus on Italian terminology. Economic vocabulary, once confined to technical registers, has increasingly entered media language and public communication. The methodology involves analyzing journalistic texts, legal documents, and official publications to identify three lexical levels—terminological, non-terminological, and general—and to explore their interaction in conveying economic information. Findings highlight the role of phraseological units and the influence of Italian and English borrowings in enriching and standardizing Albanian economic terminology. The comparative perspective underscores lexical innovation and cross-linguistic influence, while also revealing challenges of clarity and consistency in specialized discourse. From a social and educational standpoint, the study contributes to understanding how economic language shapes public awareness, supports media literacy, and fosters linguistic competence in interpreting complex economic realities.